Determination of Caesarean Section (SC) Delivery - Sumastri, Heni; Edyansyah, Erwin; Pastari, Marta (PT FORMOSA CENDEKIA GLOBAL, 2024)
There is a trend of increasing SC procedures in a number of hospitals, both in private hospitals and goverment hospitals, even though the clinical risk to mothers who give birth through SC surgery is greater than the risk of normal (vaginal) birth. Psychological risks cannot be avoided because the pain after SC surgery is longer and there are risks to the baby. The risk of adverse post-SC consequences needs to be studied further from a health ethics perspective, starting from the doctor's decision-making process in carrying out SC surgery. This research method is analytical using a cross-sectional approach (V. Wiratna Sujarweni, 2020). Time and Place of Research: Research was conducted from June-August 2023. This research was conducted at the Palembang Muhammadiyah Hospital in 2023. The number of types of birth with SC was 70 respondents and normal delivery was 26 respondents. The results of statistical tests showed that there was a significant relationship between maternal age, PEB/eclampsia, premature rupture of membranes (KPD), and gravida status, with SC delivery. From the research results it can be concluded that the type of delivery, maternal age, PEB/eclampsia, premature rupture of membranes (KPD), and gravida status, are factors that cause respondents to undergo SC delivery